Selection of target species for marine protected area: A multi criteria approach using benthic organisms - Montiel San Martin, Americo Manuel; Perez, Daniel; Gorny, Matthias (My University, 2022)
The selection of optimal target species to define and manage protected marine areas (MPAs) has generated a great scientific discussion during the past decades. Benthic invertebrates are commonly less considered as important target species, despite their pivotal role in marine ecosystems. To address this issue, we determined target species among benthic marine organisms using a multi-criteria approach. For this purpose, we used a data base from the Katalalixar National Reserve (RNK) in central Patagonia, Chile. The data were obtained through underwater photography and quantitative sampling by means of scuba diving during three expeditions between 2017 and 2019. Based on the total taxonomical inventory from both methods, a SIMPER analysis was used to determine 10 candidate species, and the Landscape Selection Species program was used for the selection of target species. Finally, eight target species were selected. The black snail Tegula atra, the hermit crab Pagurus comptus, the gastropod Crepipatella dilatata, and the polychaete Platynereis australis were selected among errant species. Among sessile species, the encrusting coralline algae Lithothamnium sp., the sea anemone Actinostola chilensis, the parchment worm Chaetopterus variopedatus, and the encrusting ascidia Didemnum sp. were the selected species. Based on our results we expect that these species will be included as target species in future management plans to improve protection of the marine environment of the Katalalixar National Reserve, one of the most pristine areas of the Chilean fjord region.
Seleção de espécies-alvo para áreas marinhas protegidas: uma abordagem multicritério usando organismos bentônicos
Keywords: Macroinvertebrates; Macroalgae; Biodiversity; Patagonia